A Banach Space Regularization Approach for Multifrequency Microwave Imaging - Claudio Estatico; Alessandro Fedeli; Matteo Pastorino; Andrea Randazzo (International Journal of Antennas and Propagation)
A method for microwave imaging of dielectric targets is proposed. It is based on a tomographic approach in which the field scattered by an unknown target (and collected in a proper observation domain) is inverted by using an inexact-Newton method developed in Lp Banach spaces. In particular, the extension of the approach to multifrequency data processing is reported. The mathematical formulation of the new method is described and the results of numerical simulations are reported and discussed, analyzing the behavior of the multifrequency processing technique combined with the Banach spaces reconstruction method.